Adjuvant incorporated lipid nanoparticles for enhanced mRNA-mediated cancer immunotherapy. (3rd December 2019) - Lee, Kyuri; Kim, Soo Young; Seo, Yunmi; Kim, Myung Hee; Chang, Jun; Lee, Hyukjin
Abstract : For mRNA mediated cancer immunotherapy, Pam3 was incorporated as an adjuvant within lipid nanoparticles (LNPs) with OVA mRNA. Abstract : For mRNA mediated cancer immunotherapy, Pam3 was incorporated as an adjuvant within lipid nanoparticles (LNPs) with OVA mRNA. The developed Pam3 incorporated LNPs showed successful expression of tumor antigens with enhanced immune stimulation. We demonstrated that the synergies of Pam3 LNPs could greatly improve the efficacy of tumor prevention by mRNA vaccines.